Association of plasma fibrinogen and development of complications in type 2 diabetes mellitus - Patel, Het V.; Sumple, Rajesh S.; Harshitha K., Pooja; R. Sumple , Kshitij (International Journal of Research in Medical Sciences, 2023)
Background: Fibrinogen is a glycoprotein produced by the liver that plays a crucial role in blood clotting. Elevated levels of fibrinogen have been associated with an increased risk of cardio vascular disease, stroke and other chronic conditions. Several studies have investigated the relationship between fibrinogen and diabetes mellitus. Furthermore, fibrinogen has been suggested to play a role in pathogenesis of diabetes and its complications by promoting inflammation and endothelial dysfunction. The aim of the study was done to study association of fibrinogen levels and development of complications of diabetes mellitus. Methods: A cross sectional observational study was conducted at medicine department of Dhiraj Hospital, Vadodara. Total of 114 diabetes mellitus patients were studied. The level of fibrinogen as well as presence of various risk factors like smoking, hypertension, obesity, dyslipidemia and different microvascular and macro-vascular complications were assessed. There were no conflict of interest. Results: Of 114 patients smoking, overweight, hypertension, uncontrolled diabetes and dyslipidemia was reported in 54.4%, 30.7%, 41.2%, 28.1% and 60.5% respectively. Microvascular complication like retinopathy, nephropathy and neuropathy was reported in 34.2%, 40.4% and 21.1% patients respectively. Macrovascular complications like coronary artery disease and stroke was reported in 20.2% and 16.7% patients respectively. Average level of fibrinogen was found higher amongst diabetic patients with microvascular as well as macrovascular complications. Conclusions: Serum fibrinogen level was found to be higher among patients with poor glycemic control, dyslipidemia, hypertension and higher BMI. A positive correlation was found between the level of fibrinogen and various complications of diabetes mellitus.